Communicating Nutrition and Other Science: It's a Management Issue. Issue 2 (March 2018) - Rowe, Sylvia B.; Alexander, Nick
Abstract : Health, nutrition, and other science communicators, for some time, have been frustrated over the inability or reluctance of policy makers and significant portions of the public to accept scientific messages around topics such as nutrition, obesity, biotechnology, genetic, vaccine, and climate science, as well as other controversial topics of public interest. To date, experts in communication have relied on their experience in developing best practices to overcome antiscience doubts and deliver accurate scientific messages. The National Academies of Science has endorsed a new approach. More than a year ago, the National Academies of Science launched a rigorous project to identify research gaps and ultimately to formulate best guidance for science communicators, particularly in communicating around controversial issues. The present article explores interim findings presented at a November 2017 conference on the Science of Science Communication.